2017
DOI: 10.1038/srep46884
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Phytosterol esters attenuate hepatic steatosis in rats with non-alcoholic fatty liver disease rats fed a high-fat diet

Abstract: Scientific Reports 7: Article number: 41604; published online: 07 February 2017; updated: 24 August 2017. This Article contains an error in the order of the Figures. Figures 3, 4 and 6 were published as Figures 4, 6 and 3 respectively. The correct Figures 3, 4 and 6 appear below as Figures 1, 2 and 3 respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multiple studies have indicated increased amounts of MDA, as measured by the TBAR assay, and OxLDL levels in human NAFLD and NASH patients in comparison to control subjects (15,(35)(36)(37)(38)(39). In addition, the presence of MDA adducts in livers has been documented for several different experimental rat and mouse models of NAFLD and NASH (40)(41)(42)(43). In line with these publications, work from our group indicated the presence of MDA adducts in livers of human NASH (44), as well as during steatohepatitis in hypercholesterolemic Ldlr −/− mice on highfat high-cholesterol diet (45), a murine model resembling human lipid profiles of NAFLD (46).…”
Section: Ose Presence In Nafldmentioning
confidence: 99%
“…Multiple studies have indicated increased amounts of MDA, as measured by the TBAR assay, and OxLDL levels in human NAFLD and NASH patients in comparison to control subjects (15,(35)(36)(37)(38)(39). In addition, the presence of MDA adducts in livers has been documented for several different experimental rat and mouse models of NAFLD and NASH (40)(41)(42)(43). In line with these publications, work from our group indicated the presence of MDA adducts in livers of human NASH (44), as well as during steatohepatitis in hypercholesterolemic Ldlr −/− mice on highfat high-cholesterol diet (45), a murine model resembling human lipid profiles of NAFLD (46).…”
Section: Ose Presence In Nafldmentioning
confidence: 99%
“…NAFLD associates with low levels of serum plant sterols in cross-sectional studies [ 3 , 4 ] and plant sterols are suggested to prevent the progression of NAFLD [ 5 ]. Plant sterols and plant stanols are normal components of plants.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it is highly relevant to understand the associations and potential causalities regarding hepatic non-cholesterol sterols and liver health. The fascinating question is why on one side dietary supplementation of both plant sterol as well as plant stanol esters seems to protect against liver inflammation in animal models for NASH [ 2 , 3 ] whereas at the same time soy-based parenteral nutrition which is rich in plant sterols results in cholestasis, elevated transaminases and bilirubin levels, and liver damage [ 4 , 5 ]. To be able to understand these effects, there is a clear need for this type of fundamental data regarding differences in plant sterol and stanol concentrations in disease conditions, but also with respect to the potential effects of changing non-cholesterol sterol concentrations in that particular disease.…”
mentioning
confidence: 99%